Dietary selenium intake and sarcopenia in American adults - Li, Jianfen; Jiang, Chaohui; Wu, Lingfeng; Tian, Jiangyan; Zhang, Bin (Frontiers in Nutrition, 2024)
The relationship between dietary selenium intake and sarcopenia remains poorly understood. This study investigates the associations between dietary selenium intake and sarcopenia among American adults.This cross-sectional study analyzed data from 19,696 participants in the National Health and Nutrition Examination Survey (NHANES) for 1999-2006 and 2011-2018. Appendicular muscle mass, assessed using dual-energy X-ray absorptiometry and adjusted for body mass index, was used as a marker for sarcopenia. Dietary selenium intake was evaluated through the 24-hour dietary recall system, and the study accounted for the complex sampling design and dietary sample weights.Results: Among the 19,696 participants, the prevalence of sarcopenia was 8.46%.Compared to the lowest quintile of dietary selenium intake (Q1, <80.10μg/day), the odds ratios for sarcopenia in the second quintile (Q2, 80.10-124.61μg/day) and the third quintile (Q3, >124.61μg/day) were 0.80 (95% confidence interval [CI]: 0.70-0.92, p=0.002) and 0.61 (95% CI: 0.51-0.73, p<0.001), respectively. A negative relationship was observed between dietary selenium intake and sarcopenia (nonlinear: p=0.285).Furthermore, sensitivity analyses revealed a robust association after further adjusting for blood selenium levels.The results suggest an inverse association between dietary selenium intake and sarcopenia among American adults.